A Review and Critique of Obsessive-Compulsive Personality Disorder Etiologies - Steven Charles Hertler (Europe's Journal of Psychology, 2014)
The present review and critique of extant etiological theories centers on a single finding: Obsessive-compulsive personality is highly heritable (0.78) and not significantly influenced by “common, shared-in-families environmental factors” (Torgersen et al., 2000, p. 424). This finding, though twelve years old, has remained dissociated from existing etiological accounts. Psychoanalytic theories anachronistically maintain that obsessive personality is familially forged. Biological theories, few, unelaborated and weakened by postulating proximate instead of ultimate explanations, fail to seriously reckon with Torgersen’s findings. Truly integrating heritability estimates into a functional etiological account of obsessive character, it is argued in the discussion section, will come from an evolutionary model that understands obsessive personality to be an evolved strategy rather than a dysfunctional disorder.